Acquiring knowledge workers in organizations - Sobocka-Szczapa, Halina (Ekonomia i Prawo. Economics and Law, 2020)
Motivation: In modern enterprises, the basic meaning — in connection with the depletion of other capital resources, and especially natural resources — is the knowledge that determines the value of human capital used in organizations. Very often, therefore, we are currently meeting the term economy based on knowledge, which means the ability of the economy to absorb and simultaneously generate processes related to shaping the competencies of human resources. It is extremely important to verify the relationship between the organization and the labor market as a source of knowledge workers acquisition. The importance of knowledge management in contemporary organizations is the result of the appearance of people with such a unique level of knowledge that they usually decide about the success of the organization’s activities. They are known as knowledge workers. Acquiring knowledge workers is now a must for all organizations, and their management. Aim: The main objective of the study is to present the category of knowledge workers in the context of knowledge management and the possibility of acquiring such employees by modern organizations. The method used in the study is a study review of the literature and statistical analysis of databases. Results: The added value of the analysis is the indication of the relationship between the